Determining the location of localized defect in the perpendicular junction configuration with the use of electron beam induced current - Phua, Poh Chin. (2009)
This paper describes a new method of determining the location of a localized defect in semiconductor materials using the perpendicular p–n junction configuration. The scanning electron